2011
DOI: 10.1007/s12471-011-0143-z
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous renal denervation for the treatment of resistant essential hypertension; the first Dutch experience

Abstract: BackgroundIn a subpopulation of patients with essential hypertension, therapeutic targets are not met, despite the use of multiple types of medication. In this paper we describe our first experience with a novel percutaneous treatment modality using renal artery radiofrequency (RF) ablation.MethodsPatients who were resistant to at least three types of antihypertensive medical therapy (office systolic blood pressure ≥ 160 mmHg; n = 9) or who did not tolerate medication (n = 2) were selected. Between July and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 14 publications
4
40
0
2
Order By: Relevance
“…Different centres have published their first clinical experiences of this promising treatment modality. [19,[28][29][30][31][32] These analyses show a similar reduction in office BP as reported in the first clinical trials. However, the effect of pRDN on ambulatory BP measurements (ABPM) differed throughout the studies.…”
Section: Results Of Prdn In Daily Practicesupporting
confidence: 63%
See 1 more Smart Citation
“…Different centres have published their first clinical experiences of this promising treatment modality. [19,[28][29][30][31][32] These analyses show a similar reduction in office BP as reported in the first clinical trials. However, the effect of pRDN on ambulatory BP measurements (ABPM) differed throughout the studies.…”
Section: Results Of Prdn In Daily Practicesupporting
confidence: 63%
“…In preclinical studies this has shown to be effective, reducing norepinephrine levels by 80-90 %, without adverse effects on the vessel wall (Ardian Inc, unpublished). [19] Clinical studies…”
Section: The Sympathetic Nervous Systemmentioning
confidence: 99%
“…
Studies employing percutaneous renal sympathetic denervation (RSD) [1][2][3][4] showed a reduction in both systolic and diastolic blood pressure (BP) among refractory hypertensive patients. As we described previously [5,6], the reduction in office BP was evident from the 1st month until one year after RSD in refractory hypertensive patients.
…”
mentioning
confidence: 99%
“…Среди побочных эффектов наблюда-лось в одном случае прогрессирование атероскле-ротического поражения почечных артерий, но не потребовавшее инвазивного вмешательства. Тем не менее, настороженность в отношении безопа-сности процедуры и отдаленных последствий по-прежнему остается.Недавно [66] были опубликованы данные о пер-вом применении данной технологии группой авторов в Дании. В 2010г было прооперировано 11 пациентов с резистентной АГ без развития каких-либо осложне-ний.…”
unclassified
“…Недавно [66] были опубликованы данные о пер-вом применении данной технологии группой авторов в Дании. В 2010г было прооперировано 11 пациентов с резистентной АГ без развития каких-либо осложне-ний.…”
unclassified